PENGARUH CARA PREPARASI DAN WAKTU PANEN TERHADAP AKTIVITAS ANTIOKSIDAN MINYAK ATSIRI RIMPANG Curcuma mangga Val. YANG DIUKUR DENGAN METODE 1,1-DIFENIL-2-PIKRILHIDRAZIL (DPPH) DAN THIOBARBITURIC ACID REACTIVE SUBSTANCES (TBARS) - , FIRMA WIDYA PANGESTIKA ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The study of antioxidant activities of the essential oil from Curcuma mangga Val. rhizomes have been done. This research aims to find out the effect of preparation method and harvest time on antioxidant activities of the essential oil of C.mangga rhizomes determined by spectrophotometric method. Variation of the sample solvents and comparison of antioxidant activities of essential oil and synthetic antioxidant were also studied. The study consisted of three stages which are sample preparation, isolation of essential oil, and antioxidant activity assay. Sample preparation of C.mangga rhizomes can be divided into wet and windâdried samples with harvest time in November and February. Furthermore, the isolations of essential oil were carried out by water and steam distillation method for 6 hours. Identification of chemical constituents of essential oil of C.mangga were done by Gas Chromatography-Mass Spectrometry (GC-MS). Antioxidant activity assays on essential oil and butyl hidroxy toluene (BHT) were performed with DPPH radical scavenging and inhibition of TBARS formation methods with solvent variations. Significant tests by ANOVA method was performed on antioxidant activities of essential oil and BHT by DPPH and TBARS methods (P < 0,05). The percentage yield of essential oil from wind-dried samples are more than that of wet samples either harvest time in November or February. The GC-MS analysis of essential oil components resulted in the identification of 25 compounds (November) and 6 compounds (February). The major constituent components of essential oil of C.mangga were Î²-myrcene and Î²-pinene. The essential oil of C.mangga showed strong antioxidant activities againts DPPH radical and TBARS formation. The antioxidant activities of essential oil and BHT with DPPH and TBARS methods didnât show significant differences.